Cellular Entry, Cytotoxicity, and Antifungal Activity of Newly Synthesized Dendrimers - Aneliya Kostadinova; Ema Gaydarska; Tanya Topouzova-Hristova; Dayana Benkova; Galya Staneva; Ekaterina Krumova; Rusina Hazarosova; Miroslav Marinov; Asya Tsanova; Albena Jordanova; Ivo Grabchev (Applied Sciences)
Dendrimers, 4-dimethylamino-1,8-naphthalimide (DAB) and its halogenated analog 3-bromo-4-dimethylamino-1,8-naphthalimide (DAB-Br), were evaluated on eukaryotic cells, human HFF-1 fibroblast cells, and five fungal species. Although both dendrimers have demonstrated antibacterial and antiviral potential, thus far, their effects on eukaryotic cells, particularly human and fungal cells, have not been investigated. For this purpose, their cytotoxicity, mechanisms of cellular entry, and antifungal activity were studied. Dynamic light scattering measurements revealed that both dendrimers exhibited positive surface charges (+28 to +35 mV), good colloidal stability, and nanoscale dimensions (117–234 nm), facilitating interactions with target cells. The MTT assay showed that DAB was more cytotoxic toward HFF-1 cells (IC50 = 27 µg/mL) compared to DAB-Br (IC50 = 68 µg/mL). In contrast, the resazurin-based antifungal assay demonstrated that DAB-Br had superior antifungal activity, achieving a lower minimum inhibitory concentration (0.148 µg/µL), compared to DAB (0.295 µg/µL). A trypan blue exclusion test revealed that both dendrimers entered cells through membrane permeabilization, either temporarily or permanently, depending on the concentration and exposure time. At concentrations above 30 µg/mL, irreversible permeabilization was observed within two hours of treatment, accompanied by a decrease in membrane lipid order, indicating altered membrane integrity and permeability. Conversely, at lower concentrations (7.5–15 µg/mL), dendrimers induced only temporary membrane permeabilization, with membranes remaining intact, suggesting a reversible interaction with the lipid bilayer. Conducting thorough and systematic research to fully explore their biological activities could provide valuable insight for future applications.